Pancreatite aguda como manifestação de linfoma de Burkitt em idade pediátrica. - Filipe Glória Silva; Mafalda Paiva; Ana Tavares; Ana Lacerda; Gabriela Pereira; António Marques; Deolinda Barata; José Cabral (Acta Médica Portuguesa, 2008)
Pancreatitis in children and adolescents is uncommon and its causes are more varied in this age group than in adults. A tumoral aetiology is particularly rare. We present the case of a 13-year-old boy who was admitted to our Intensive Care Unit with the diagnosis of acute pancreatitis, bilateral pleural effusion and ascites. Serial sonographic and computed tomography evaluations were suggestive of an infiltrative process of the gastric wall. Endoscopy showed an infiltrative tumor of the gastric mucosa and duodenum with a giant ulcer. Biopsies were compatible with Burkitt Lymphoma confirmed by ascitic fluid cytology and cytometry. Because of severe progressive cholestasis a temporary biliary stent was placed in the common bile duct. After staging (stage III), the patient was treated according to FAB LMB 96 chemotherapy protocol, achieving complete remission. Acute pancreatitis and cholestasis are rare presentations of lymphoma in the paediatric age group.